When violence begins at home : a comprehensive guide to understanding and ending domestic abuse (Alameda, CA : Hunter House, 2005)
"Resource for victims of abuse and their caregivers, significantly updated with guidance on everything from indicators of an abusive relationship to domestic violence legislation, as well as information on date rape drugs, cyber-stalking, effectiveness of batterer intervention programs, and more"--Provided by publisher.
Introduction -- The dynamics of abusive relationships -- The effects of family violence on children -- Teen dating violence -- The intimate relationship between substance abuse and domestic violence -- Battered women and the legal system -- Living underground -- The oppression that binds : barriers to living violence free -- Friends, family, and loved ones : when someone you know is being hurt -- Domestic violence and the workplace -- Battered women and their health : the response of the medical community -- Battered women and communities of faith -- Domestic violence and the military -- Creating a community response to domestic violence -- Intervention strategies for battered women and their children -- Advocacy and empowerment -- Intervention and prevention programs for batterers -- Loving ourselves : self-care for helpers -- The national domestic violence hotline -- A history of violence against women.
Includes bibliographical references and index.
Keywords: Wife abuse -- United States; Wife abuse -- United States -- Prevention; Family violence -- United States